Multimodal Strategies of Children’s Exploratory Engagement in The Digital Discourse of British Museums - Biliuk, Julia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The integration of digital technologies into museums has transformed approaches to communication with audiences, particularly children. Museum websites today function as autonomous environments for representing cultural and natural heritage, where multimodality is a key principle. In digital museum communication, child-oriented multimodality emerges as a promising area of research. The relevance is determined by the need to understand how multimodal practices reshape the role of children, shifting them from passive recipients to active participants in cultural communication. This study analyses how the multimodal resources of museum websites construct exploratory interaction with cultural heritage for young audiences, showing how leading institutions employ strategies that position children as active participants in cultural communication and learning. The research employs qualitative multimodal discourse analysis, combining structural-semiotic observation with comparative analysis of web interfaces and educational content across institutions. Based on the analysis of the British Museum, the Natural History Museum, and the National Gallery websites, the findings demonstrate that sensory backpacks, interactive guides, creative challenges, and edutainment activities provide opportunities for children to explore exhibits and actively engage with the museum environment. Narrative framing of activities combines tactile, auditory, and visual engagement, while interactive elements extend communication across channels and create a digital atmosphere of curiosity, participation, and emotional connection. Such practices highlight the growing role of digital platforms as spaces where museums test new pedagogical and communicative models tailored to younger audiences. In this perspective, museum websites function as repositories of information and at the same time as curated multimodal spaces where play, interpretation, and exploration shape communication with children. Emphasising children’s multimodal engagement opens new forms of interaction with heritage, strengthens participatory practices, and reflects broader transformations of institutional identity in the digital age, ensuring sustainable engagement of future audiences.